Bone marrow and haematopoietic cell transplantation - Hołowiecki, Jerzy (Contemporary Oncology/Współczesna Onkologia, 2000)
The concise history of BMT development world-wide and in Poland is presented. BMT evolved over a period of 50 years. In Poland BMT has been routinely performed for more than 10 years and in this time the number of transplants rose from 6 in 1989 to over 600 planned for year 2000. The above was accomplished thanks to successive founding of the 14 active BMT centres, which currently perform from 10 to over 130 BMT’s per annum (mean 34). The results achieved in Poland correspond to results obtained world-wide and reported to IBMTR and EBMT registries. In relation to other European countries the number of teams and the number of BMT procedures performed per annum in Poland is by 1,5 times lower. For the nearest future a better access to URD BMT’s appears to be the the most important problem.